2020
DOI: 10.1016/j.jtho.2019.12.128
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Homozygous Deletions of Type I Interferon Genes in Pleural Mesothelioma Confer Sensitivity to Oncolytic Measles Virus

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 39 publications
7
54
0
Order By: Relevance
“…The red module negatively correlated with CDKN2A/2B loss enriched genes of anti-viral type I interferon (IFN-I, mainly IFN-α and IFN-β) signaling pathway, suggesting a link between CDKN2A/2B inactivation and impaired IFN-I pathway ( Figure 2 E–G and Figure S2D ). To explore the underlying mechanisms, we analyzed co-occurring alterations in MPM samples, which revealed that CDKN2A and genes of the IFN family were significantly co-deleted ( Figure 2 H), consistent with a recent study, showing that defects in the IFN-I pathway mainly co-occur with CDKN2A loss [ 14 ].…”
Section: Resultssupporting
confidence: 85%
“…The red module negatively correlated with CDKN2A/2B loss enriched genes of anti-viral type I interferon (IFN-I, mainly IFN-α and IFN-β) signaling pathway, suggesting a link between CDKN2A/2B inactivation and impaired IFN-I pathway ( Figure 2 E–G and Figure S2D ). To explore the underlying mechanisms, we analyzed co-occurring alterations in MPM samples, which revealed that CDKN2A and genes of the IFN family were significantly co-deleted ( Figure 2 H), consistent with a recent study, showing that defects in the IFN-I pathway mainly co-occur with CDKN2A loss [ 14 ].…”
Section: Resultssupporting
confidence: 85%
“…The bi-allelic deletion of the CDKN2A gene, further confirmed in a list of MM human cell lines including the least invasive MM34 (Meso 34), was found to be strongly associated with overexpression of IL34 and weakly with mutations of the NF2 gene (with no association with other genetic alterations in BAP1 , LATS2 or TP53 genes) [ 16 ]. MM163 (Meso 163) differed from MM34 by a homozygous deletion of the IFNB1 gene (located in the same 9p21.3 chromosome region as CDKN2A ) that encodes IFN-β [ 17 ]. A transcriptomic analysis of the group of human MM cell lines sharing the same features as MM163, comparing cells exposed to measles virus with untreated cells, revealed these cells were characterized by a weak IFN-I response, some canonical pathways involved in antigen presentation and cytotoxic T lymphocyte-mediated apoptosis of target cells being particularly hit [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…MM163 (Meso 163) differed from MM34 by a homozygous deletion of the IFNB1 gene (located in the same 9p21.3 chromosome region as CDKN2A ) that encodes IFN-β [ 17 ]. A transcriptomic analysis of the group of human MM cell lines sharing the same features as MM163, comparing cells exposed to measles virus with untreated cells, revealed these cells were characterized by a weak IFN-I response, some canonical pathways involved in antigen presentation and cytotoxic T lymphocyte-mediated apoptosis of target cells being particularly hit [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two patients with MPM and one with LUAD had codon 12/13 mutations, while one patient with MPM and two with LUAD had codon 61 mutations. We next used Affymetrix CytoScanHD Arrays to identify copy number alterations of the KRAS locus in a cohort of primary MPM cell lines from Nantes, France (GEO dataset GSE134349) 39,40 . We found gains in ten and losses in two of 32 MPM cell lines examined, which was statistically significantly more that what was reported in two previous studies of MPM tumours 22,41 (Fig.…”
Section: Identification Of Kras Mutations In Human Mpm Patientsmentioning
confidence: 99%
“…Declaration and were prospectively approved by the University of Nantes Ethics Committee (approval #xxxx). All patients gave written informed consent a priori.MPE samples from 61 patients with MPM were used to generate cell lines, as described elsewhere39,40 . Genomic DNA from 32 MPM cell lines was extracted with Kras tm4Tyj /J (KRAS G12D ; #008179)44 , and B6.129P2-Trp53 tm1Brn /J (Trp53f/f; #008462)45 mice were obtained from Jackson Laboratories (Bar Harbor, ME) and bred on the C57BL/6 background at the University of Patras Center for Animal Models of Disease.…”
mentioning
confidence: 99%